PEMBERDAYAAN PEREMPUAN KORBAN ANAK YANG DILACURKAN DI KAWASAN EKS LOKALISASI PANTAI HARAPAN PANJANG KOTA BANDAR LAMPUNG - Eha Saleha (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2017)
This study saw efforts to empower women victims AYLA (prostituted children) in the area of the former localization Pantai Harapan Panjang Bandar Lampung City and the factors supporting and hindering development activities undertaken by non-governmental organizations (NGOs) Children's Crisis Centre (CCC) and conducted by the Women's Empowerment and child Protection (BPPA) and the Department of Social Lampung Bandar Lampung. This study uses a qualitative method with case studies of collective research strategies AYLA 130 female victims. The results showed that empowerment is the care and counseling of victims AYLA do with activities to help the victims when dealing with pimps or perpetrator, victim assistance when dealing with cases in the police and the courts, victim support when counseling with a psychologist / counselor, assistance when medical examination, when the victim assistance courses, training, apprenticeship and discussions, accompaniment of victims to return to a new place or return to its original place. Training for 130 victims of AYLA managed by NGOs CCC include: culinary training, dance training, hairdressing and computer training. Financial aid amounting to 1.5 million and 5 million Rupiah. Inhibiting factor is the empowerment of trauma and habits, economic factors, broken home and the budget is not enough of BPPA and Social Service Bandar Lampung. While the supporting factors of empowerment are all elements to support and assist the process of mentoring. Keywords: Empowerment, Women, Children prostituted